PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VIII SEMESTER II SMPN 5 SIAK KECIL KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - Salfilla Juliana (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This study is based on the low learning outcomes of students' science can be seen from the results of sciencelearning class VIII SMP Negeri 5 Siak Kecil, with grade grade average of 62.11. Therefore, the researchersprovide alternative learning with the application of guided inquiry model. SMP Negeri 5 Siak Kecil languagelesson year 2014/2015. This study aims to improve student learning outcomes of grade VIII SMP Negeri 5 SiakKecil Kecamatan Siak Kecil with the application of guided inquiry learning model. The form of researchconducted is Classroom Action Research (PTK) with 2 cycles. Based on the analysis of research data afterapplying the guided inquiry learning model, the average percentage of teacher activity in cycle I 58.75%increased to 85% in cycle II. The average percentage of student activity also increased ie 51.25% in the firstcycle increased to 81.25% in cycle II. Student learning outcomes on the basic score with the average class of62.11 and in the first cycle increased with the average class of 67.42 with the percentage increase in learningoutcomes 8.54% and the percentage of students who completed 61.53%, and in the second cycle increased. . .again with an average value of 75.80 with a percentage increase in learning outcomes by 22.04% and thepercentage of students who completed 84.61%. The results of this study indicate that the implementation ofguided inquiry learning model can improve the learning outcomes of science students of grade VIII SMP N 5Siak Kecil.